Comunicação, consumo e memória: uma escuta sobre as narrativas radiofônicas de José Medina na década de 1940 - Pasqualin, Vera da Cunha (2015)
This dissertation centers around the radio narrative work authored by José Medina in the years 1946 and 1947, in the city of São Paulo, which allows one to investigate the relationship between memory and consumption. The research material includes five radio play scripts presented in two different media: radio and newspaper. The general objective is to present the narrative structures and melodramatic production logics found in the work of José Medina, and thereby bring to mind certain habits and consumption practices, both symbolic and material, in São Paulo, in 1946 and 1947. Specific objectives include presenting the mediatic production of José Medina besides his radio production, and study the radio language used at the time. The question used as the basis for the research is intended to show how the narrative construction and the radio language evidence the memory of certain habits and consumption practices in São Paulo in 1946 and 1947. As this is a historical research that counts on a broad documental corpus, the method used was the document analysis and bibliographic survey. The main sources of the survey to gather together the corpus were the Medina family files and the Public Archives of the State of São Paulo. Theoretical references include scholars such as Paul Zumthor, Murray Schafer, Marlyse Meyer, Ian Watt, Edgar Morin, Jerusa Pires Ferreira, Mônica Rebecca Ferrari Nunes, Ecléa Bosi, Néstor García Canclini, Jesús Martín-Barbero and Roger Silverstone, and other researchers that were used as guidance for these reflections. Results point to the intertwining of communications, consumption, and memory, looking at radio listening and the reading of radio plays scripts in the newspaper as symbolic assets that represent media consumption and position the listener/reader in time and space.